A Season of Unusual Depression: The Panic of 1857 and the Crisis of City Government in Toronto - Jarvis, Eric (Ontario History, 2020)
The Panic of 1857 had a significant impact on Toronto, since the economic depression that followed affected the city’s government, fiscal health, and public services. Thus, it can be used as a case study of how a 19th century Panic and depression could change a city’s society, even to the point of “crisis”. Using city records and newspapers, this analysis focuses on city debt management, tax collection and cutbacks on such new services as police, fire-fighting and street lighting. In addition, it discusses how a Panic could transform democratic politics by decreasing the number of persons eligible for city council and the franchise. The mayor ceased to be an elected position. Such “reforms” would be used again following the more famous reforms of the 1890s depression. In fact, a pattern can be discerned: city democracy was increased by boom times and decreased by depressions.